Structural applications of synthetic fibre reinforced cementitious composites: A review on material properties, fire behaviour, durability and structural performance. (December 2021) - Chandrathilaka, E.R.K.; Baduge, Shanaka Kristombu; Mendis, Priyan; Thilakarathna, P.S.M.
Abstract: Though fibres are being used in concrete structures for a couple of decades, the use of polymeric Synthetic Fibres (SyF) such as Polypropylene Fibre (PPF), Polyethylene Fibre (PEF) and Polyvinyl-alcohol Fibre (PVAF) found more rapid growth in recent years. The higher durability and physical properties of SyF increased its use in concrete despite there are some drawbacks in mechanical performances. However, the development of high modulus SyF and the use of hybrid Fibre Reinforced Concrete (FRC) systems helped to mitigate the mechanical performance drawbacks to produce superior Synthetic Fibre Reinforced Concrete (SyFRC) to use in structural elements. This paper presents the recent developments and applications of SyFRC in structural elements along with the material properties such as mechanical, fire and durability performances of SyFRC.